TJNPR 2019
DOI: 10.26538/tjnpr/v3i5.5
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Cytotoxic Activity of Sutherlandia frutescens and Carpobrotus edulis on Malignant glioblastoma Cells

Abstract: Glioblastoma (GBM) is the most common and aggressive intracranial tumour with limited therapeutic options due to their high tumour vasculature and invasiveness. Treatment of GBM includes surgery, followed by chemotherapy and radiotherapy. Despite these treatment options, tumour relapse is still a major issue hence the need for cheap and effective treatment strategies. South Africa is endowed with numerous medicinal plants including Sutherlandia frutescens (S. frutescens) and Carpobrotus edulis (C.edulis), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A clonogenic assay was performed to assess the ability of cancer cells to divide and form colonies after treatment with the IC 50 of the crude product and fractions of H. opposita leaf using previously described methods (27). The cells were seeded in 6 cm dishes according to their density, treated for 48 h at their IC50, trypsinized, resuspended in 2 mL of culture media, counted, and reseeded at 500 cells/dish (35 mm).…”
Section: Clonogenic Determination Of the Crude Extracts And Fractionsmentioning
confidence: 99%
“…A clonogenic assay was performed to assess the ability of cancer cells to divide and form colonies after treatment with the IC 50 of the crude product and fractions of H. opposita leaf using previously described methods (27). The cells were seeded in 6 cm dishes according to their density, treated for 48 h at their IC50, trypsinized, resuspended in 2 mL of culture media, counted, and reseeded at 500 cells/dish (35 mm).…”
Section: Clonogenic Determination Of the Crude Extracts And Fractionsmentioning
confidence: 99%
“…This study showed that the ethanol-water extract significantly decreased cell viability after 24-h incubation compared to the aqueous extract [36], and this anti-proliferative effect could be attributed to the constituents, especially the seven major phenolics: sinapic acid, ferulic acid, luteolin 7-O-glucoside, hyperside, isoquercitin, ellagic acid, and isorhamnetin 3-O-rutinoside. A recent in vitro preliminary cytotoxicity study on the effects of C. edulis on U251 and U87 malignant glioblastoma cell lines showed that the extract elicits an anti-proliferative property and also inhibited colony formation in U251 cells [80].…”
Section: Antiproliferative Propertiesmentioning
confidence: 99%